Ultrasound‐Guided Release of the Tibial Nerve and Its Distal Branches: A Cadaveric Study. (27th December 2018) - Iborra, Álvaro; Villanueva‐Martínez, Manuel; Barrett, Stephen L.; Rodríguez‐Collazo, Edgardo R.; Sanz‐Ruiz, Pablo
Abstract : Objectives: The purpose of the study was to determine whether ultrasound (US)‐guided surgery is a viable type of surgery for performing an effective release/decompression of the constricting structures that are responsible for focal nerve compression in tarsal tunnel syndrome. Methods: Ultrasound guidance was used on cadaveric specimens to delineate the anatomic course of the nerves and vessels in the medial ankle that comprise the structures involved in tarsal tunnel syndrome. Ultrasound guidance was used on cadaveric specimens and assisted in delineating a safe surgical zone to adequately and effectively release these constrictive structures of the proximal and distal tarsal tunnels. The US‐guided tarsal tunnel release/decompression was performed through 2 small 1‐ to 2‐mm portals. After US‐guided release, anatomic dissection was used to check the efficacy (release of the flexor retinaculum and deep abductor hallucis muscle) and safety (absence of neurovascular or tendon injury) of the procedure. Results: In 12 fresh cadaveric specimens, US‐guided release of the tibial nerve (proximal tarsal tunnel) and its branches (distal tarsal tunnel) at the medial ankle was effective in all 12 specimens (100% release rate), without any signs of compromise or injury into the neurovascular structures. Conclusions: Ultrasound‐guided tarsal tunnel release is a feasible surgical procedure that can be safe and effective with the proper training, although further investigation is warranted. This type of surgery may promote faster recovery with less postoperative morbidity, including pain, but this will be the subject of a further investigation.